Lojalność pracownicza w organizacjach międzynarodowych - studium przypadku - Piórkowska-Wojciechowska, Katarzyna (Employee loyalty in the international organization - case study, 2006)
The article presents the results of chosen aspects of research on employee loyalty in the international organization. In fact, in the article the following issues are presented: research methodology, the concept of employee loyalty, the conditions of employee loyalty and particular results of research dealing with the level of employee loyalty and its psychological, personal and organizational conditions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 119-128